(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Nurses represent the backbone of any health care system. Today in the fight against Covid-19, several nurses find themselves on the frontline. This report is a clear reminder of their important position and a wake-up call to ensure that they receive the help they need to keep the planet safe. 1 Nurses play a very important function, locally as well as internationally. They are on the front lines, day in and day out, taking care of these patients. “They are able to see what is working, as well as things that can be done differently to provide more effective and efficient care, and offer suggestions for improvement.” 2020 is recognized by the World Health Organization as the Year of the Nurse and Midwife – On the function of nurses in the preparation and reaction to disasters. (World Health Organization) Globally, the way the world views nurses and health care professionals already changes. Because not everyone knows what is happening in a health care facility, the COVID-19 pandemic is high The COVID-19 pandemic has brought nurses to the forefront of people’s minds and there is a daily capture of the media attention and public gratitude to health care professionals.2 This short communication concludes with the key role of nurses for effective management during covid-19 pandemics.